Pulse rate and blood pressure changes during low-irradiance PDT compared with conventional PDT in the treatment of facial actinic keratoses: a retrospective study - Keller, Aric; Hartmann, Julia; Enk, Alexander; Gholam, Patrick (Photodermatology, photoimmunology & photomedicine, 2022)
Conventional photodynamic therapy (c-PDT) is a highly effective treatment for actinic keratoses. Besides pain as the main side effect, blood pressure (BP) increases and hypertensive crises may occur during treatment. Reducing the irradiation intensity while keeping the total dose constant (low-irradiance PDT) can achieve a clinically relevant reduction in pain. This study aimed to evaluate the influence of li-PDT on the BP and pulse (PR) during therapy and the incidence of post-interventional hypertension compared with c-PDT.
Online veröffentlicht am 30. Dezember 2021
Gesehen am 14.11.2023